Nano-enabled agriculture: How do nanoparticles cross barriers in plants? - Wu, Honghong; Li, Zhaohu (Plant communications, 2022)
Nano-enabled agriculture is a topic of intense research interest. However, our knowledge of how nanoparticles enter plants, plant cells, and organelles is still insufficient. Here, we discuss the barriers that limit the efficient delivery of nanoparticles at the whole-plant and single-cell levels. Some commonly overlooked factors, such as light conditions and surface tension of applied nano-formulations, are discussed. Knowledge gaps regarding plant cell uptake of nanoparticles, such as the effect of electrochemical gradients across organelle membranes on nanoparticle delivery, are analyzed and discussed. The importance of controlling factors such as size, charge, stability, and dispersibility when properly designing nanomaterials for plants is outlined. We mainly focus on understanding how nanoparticles travel across barriers in plants and plant cells and the major factors that limit the efficient delivery of nanoparticles, promoting a better understanding of nanoparticle–plant interactions. We also provide suggestions on the design of nanomaterials for nano-enabled agriculture. A better understanding of how nanoparticles enter plants, plant cells, and organelles is important for facilitating the development of nano-enabled agriculture. This review discusses how nanoparticles travel across barriers in plants and plant cells and the main factors that limit the efficient delivery of nanoparticles in plants. Some suggestions about the proper design of nanomaterials for nano-enabled agriculture are provided in this review.